Subsistence agriculture in Central and Eastern Europe; how to break the vicious circle?: studies on the agricultural and food sector in Central and Eastern Europe - Abele, S.; Frohberg, K. (2003)
Subsistence agriculture is probably the least understood and the most neglected type of agriculture. In a globalised, market-driven world, it remains at the same time a myth and a marginal phenomenon. CONTENTS: Subsistence Agriculture in Development: Its Role in Processes of Structural Change; Franz Heidhues, Michael Brüntrup. Institutions and Technologies for Subsistence Agriculture: How to Increase Commercialization; Zvi Lerman. Policy Options to Overcome Subsistence Agriculture in the CEECs; Joachim von Braun, Daniela Lohlein. Decision Making Patterns of Subsistence Farmers in Bulgaria; Plamen Mishev, Philip Kostov. Commercialisation of Subsistence Agriculture in Transition Economies: On Imperfect Competition, Market Development and Support Policies; Ernst-August Nuppenau. Development Perspectives of Subsistence Farms in Southeastern Poland: Social Buffer Stock or Commercial Agriculture? Martin Petrick, Ewa Tyran. The Market Potential and Patterns of Contemporary Agriculture in Romania's Northwestern Plain; Csaba M. Kovács. Subsistence Farming in Bulgaria: Between Tradition and Market Requirements; Diana Kopeva, Nivelin Noev. The Significance of Subsistence Farming in Georgia as an Economic and Social Buffer; Hannah Kegel. Agrarian Reform and Subsistence Agriculture in Russia; Vladimir Yefimov. Economic Background and Development Opportunities of Individual Subsidiary Holdings in the Ukraine: Some Empirical Evidence; Andriy Nedoborovskyy. Modeling Subsistence Agriculture in Russia: Effects of Total Productivity Changes and Reduction of Marketing Margins; Peter Wehrheim, Peter Wobst